Development in Setu Babakan Tourism Village As A Betawi Icon in Modern Times - Prasetya Mahardika, Graha; Kusumo, Elang (Jurnal Multidisiplin Indonesia, 2024)
This study aims to explore the potential possessed by Setu Babakan Tourism Village in maintaining and developing Betawi Cultural identity in the modern era. Setu Babakan Village is known as one of the leading cultural tourism destinations in Jakarta, which promotes art, music, dance, culinary, and typical Betawi traditions. In the context of globalization and technological development, this study aims to analyze how Setu Babakan Village utilizes its cultural potential to maintain its status as an icon of Betawi Culture. We discussed the efforts of local communities and government support, as well as the challenges faced in safeguarding cultural heritage and promoting it to present and future generations. This research provides insight into the importance of preserving local culture amid the ongoing flow of modernization and globalization. The foundation of this research concept uses the A5 concept (Attractions, Accessibility, Accommodation, Activities, Amenities). The method used in this study is qualitative descriptive. Techniques for determining informants use purposive techniques in data collection using interviews, observation, and documentation techniques. The results of the study show that the development of tourism in Setu Babakan Tourism Village is optimal. However, there are still things that can be improved from each of these components.